THE EFFECT OF GLOBALIZATION ON NATIONAL SECURITY - Pooja,; Amanpreet, (International Journal of Psychosocial Rehabilitation, 2021)
National security now-a-days is a much broader and comprehensive concept that, apart from military security, takes into account all dimensions affecting human security with inclusive consideration to all elements of the national power of a nation-state. Similarly, globalization means interdependence, advancing integration, and homogenization of the world. Globalization has assumed profound power this century, which captures the opinion that happenings in one part of the globe will have significant influence on the regions and the world at large. This research article will explore several dimensions of notion of globalization, its linkages and effects on national security